Ideas of Eurasianism in the empire of Genghis Khan in the western sources (On the writings of Marco Polo) (Journal of actual problems of jurisprudence, 2018)
The article deals with the idea of Eurasianism prevailed when a descendant of Genghis Khan Khubilai in the sources of Marco Polo. One of the indisputable evidence that the basis of state-building and social order of the Mongol-Turkic empire created by Genghis Khan was the idea of Eurasianism with all its institutions is the freedom of religion, a flexible system of public administration that created and expanded opportunities Empire transforming it into the truth of the largest countries in the continent. The problem of European sources of this era is biased, which for many centuries prevailed in the relations of the empire of Genghis Khan. However, in the writings of Marco Polo apparent attempt to consider the empire from within. Due to its in-depth analysis the researcher comes to the conclusion that a great nation is not only a bastion of power, but also an important center of cultural influence, which is actively applied in the public administration system. Refuting all the speculation, which related to the great empire he is looking for the secret of the success of the state.Key words: empire, Eurasianism, religious freedom, cultural influence.